Growth rate of farmed Mangrove oysters (Magallana bilineata) at Laucala Bay, Suva, Fiji - Melody S. Vanukon Vanukon; Jasha Dehm; Timothy Pickering; Moape Kania; Ciro Rico; Chinthaka Hewavitharane (Airlangga University, 2023)
The cultivation of oysters has a significant historical background in the South Pacific region. The cultivation of pearls has been a significant source of livelihood for numerous island nations. Despite the significant cultural, dietary, and subsistence value of bivalve molluscs among Pacific Islanders, there has been limited advancement in the aquaculture of edible oysters in To enable a comprehensive assessment of the viability of cultivating edible oysters in Fiji, an estimation was conducted pertaining to the growth rate of mangrove oysters Magallana bilineata. A total of 105 oyster spat were cultured in Laucala Bay, Suva, Fiji, over the course of one year, from January 25th, 2021 to January 26th, 2022. The investigation documented exponential growth in oysters, with measurements of 87.3 ± 1.0 mm in length, 67.4 ± 0.7 mm in width, 49.8 ± 0.6 mm in depth, and 104.90 ± 22.6 g in weight. The findings of the study indicated the occurrence of positive isometric growth in relations to weight, length, width, and depth. The observed survival rate was 94%. The growth rates observed in oyster farming in Fiji exhibit similarities to those documented in other geographical locations, thereby providing a favourable indication for the progress of oyster aquaculture in the region.